Observation of interacting polaronic gas behavior in Ta-doped TiO2 thin films via terahertz time-domain spectroscopy - Cheng, Liang (2021)
Transparent conductive oxides (TCOs)—materials that have the twin desirable features of high optical transmission and electrical conductivity—play an increasingly significant role in the fields of photovoltaics and information technology. As an excellent TCO, Ta-doped anatase TiO2 shows great promise for a wide range of applications. Here, terahertz time-domain spectroscopy is used to study the complex optical conductivity r~ðxÞ of the TCO—heavily Ta-doped TiO2 thin films with different Ta-doping concentrations, in the frequency range of 0.3–2.7 THz and the temperature range of 10–300 K. Fitting the complex optical conductivity to a Drude-like behavior allows us to extract the temperature dependence of the effective mass, which suggests the existence of many-body large polarons. Moreover, the carrier scattering rate of Ta-doped TiO2 with different carrier concentrations agrees with the interacting polaron gas theory. Our results suggest that with increasing electron density in TiO2, the interaction between polarons is larger and electron–phonon coupling is smaller, which is beneficial for achieving high mobility and conductivity in TiO2.